2000
DOI: 10.1007/s005350050331
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous loss of hepatitis B surface antigen in chronic carriers, based on a long-term follow-up study in Goto Islands, Japan

Abstract: Annual mass examination was performed between 1972 and 1997 in Tomie-town, Goto Islands, Japan, where hepatitis B virus (HBV) infection is very prevalent. In the present study, the incidence of spontaneous loss of hepatitis B surface antigen (HBsAg) in HBsAg carriers was determined in this area. Three thousand and nineteen inhabitants were tested for HBsAg two or more times in our annual surveys. Among them, 131 (4.3%) were defined as chronic HBsAg carriers based on the persistence of HBsAg for 1 or more years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 24 publications
4
22
3
Order By: Relevance
“…During the study, 10 carriers (4%) became HBsAg-negative. In line with this finding, previous studies reported a positive-to-negative seroconversion rate of 2.7% (10), 6% (11), and 3.1% (12).…”
Section: Discussionsupporting
confidence: 84%
“…During the study, 10 carriers (4%) became HBsAg-negative. In line with this finding, previous studies reported a positive-to-negative seroconversion rate of 2.7% (10), 6% (11), and 3.1% (12).…”
Section: Discussionsupporting
confidence: 84%
“…These studies mainly concentrate on documenting the presence or absence of HBV and disease outcome of the patients without case-matching control groups of patients without HBsAg seroclearance. According to the results from several controlled studies [17•, 18,19], the following factors are associated with a higher chance of spontaneous HBsAg seroclearance: increasing age, anti-HBe positivity, HBV genotype A compared with genotype D, and genotype B compared with genotype C. However, gender and liver biochemistry were not the predictive factors for HBsAg seroclearance [19].…”
Section: Are There Any Predictive Factors For Hbsag Seroclearance?mentioning
confidence: 93%
“…A fixed-effect metaanalysis was conducted for studies that reported spontaneous HBsAg loss during long-term follow-up and derived 0.9% transition probability [37,38]. Besides, studies showed that HBsAg clearance under NA treatments is confined to those with an active immune response to HBV, such as HBeAg-positive patients who achieve HBeAg clearance [39].…”
Section: Hbsag Seroclearancementioning
confidence: 99%
“…Recent studies estimated that baseline HBsAg clearance was 1% to 2% among asymptomatic HBsAg carriers (mostly seropositive for anti-HBe) with a mean age of 33 years [37]. A fixed-effect metaanalysis was conducted for studies that reported spontaneous HBsAg loss during long-term follow-up and derived 0.9% transition probability [37,38].…”
Section: Hbsag Seroclearancementioning
confidence: 99%